Diseño de un manual de funciones para el mejoramiento del proceso de selección de personal en la Empresa Creaciones Juventus S.A en el año 2017. - Peña Castro, Santiago Xavier (2018)
Within the company C.JUVENTUS SA located in Quito - Ecuador, the creation and implementation of a manual of functions is of utmost importance to have a clear picture of the positions and functions that exist within the organization and to demonstrate the different activities that each one of their collaborators do. The positions are distributed from managements, sub-managements, headquarters, sales and administrative. The importance of generating and printing this type of manual will make it easier for us to solve other difficulties that can generate difficulties such as overwork or too much workload that can cause problems among collaborators etc. Bearing in mind that the functions manual is a standardization tool for the activities within an organization, it is of vital importance to have a guide, where you can obtain information about each existing carago in the company so that you can identify how the activities are carried out. the same. With the creation and implementation of the functions manual, it is a first step to create what is a department of human talent, for the same fact that having bases on the functions performed by all collaborators will give a more wide of how the organization is structured and begin to debug and carry out activities that do not have a benefit for the organization and the employee. Proposals: More efficient induction processes Empowerment of the worker in his activities Equal distribution of workload Debugging in the duplication of activities Decrease of tasks without value With the opening of this basic process you can start to make a series of new implements to the pro of the company such as: 4 Create a good process of selection of personnel, with a guide that is the manual of functions bringing satisfactory benefits to the organization so that the selection is of optimum quality improving the productivity of the company. Performance evaluations, with this guide that would make a manual of functions allows us to carry out this type of process since we have the bases of the activities or functions that each of the collaborators must carry out and see how it is developed according to the stipulated in the manual. It should be noted that there is no specialized department in human resources, since all this process had to be carried out directly by the owner of the same, taking all kinds of decisions, as identification of the problems that were made within the institution could be observed that as a priority it is to begin with the creation of a manual of functions where the activities of each job position are specified. The positions are distributed from managements, sub-managements, headquarters, sales and administrative. The importance of generating and printing this type of manual will make it easier for us to solve other difficulties that can generate difficulties such as overwork or too much workload that can cause problems among collaborators etc.